Microneedle-based device for the one-step painless collection of capillary blood samples. (March 2018) - Blicharz, Timothy; Gong, Ping; Bunner, Bernard; Chu, Larry; Leonard, Kaela; Wakefield, Jessica; Williams, Richard; Dadgar, Maisam; Tagliabue, Carlo; El Khaja, Ragheb; Marlin, Stephanie; Haghgooie, Ramin; et al.
Abstract The advancement of point-of-care diagnostics and the decentralization of healthcare have created a need for the simple, safe, standardized and painless collection of blood specimens. Here, we describe the design and implementation of a capillary blood-collection device that is more convenient and less painful than a fingerstick and venepuncture, and collects 100 µl of blood. The technology integrates into a compact, self-contained device an array of solid microneedles, a high-velocity insertion mechanism, stored vacuum, and a microfluidic system containing lithium heparin anticoagulant. The use of the device requires minimal training, as blood collection is initiated by the single push of a button. In a clinical study involving 144 participants, haemoglobin A1c measurements from device-collected samples and from venous blood samples were equivalent, and the pain associated with the device was significantly less than that associated with venepuncture. The device, which has received premarket clearance by the US Food and Drug Administration, should help improve access to healthcare, and support healthcare decentralization. A compact, self-contained device bearing an array of microneedles collects 100 μl of blood at the push of a button, and is more convenient and less painful than a fingerstick and venepuncture.